Multi-Track Diplomacy of the Joint State Actor and Non-State Actor Proposed the Maros Pangkep Geopark to Become a UNESCO Global Geopark - Dwi Putro; Tulus Warsito (Journal of Islamic World and Politics)
The Maros area has been initiated to be developed into a national geopark in 2015, then to maintain, protect, preserve and be recognized globally. The Maros area is proposed to become a UNESCO Global Geopark in 2021. This research aims to understand the process of the government, stakeholders, and the community around the geopark proposed that the Maros Geopark become a UNESCO Global Geopark (UGG). This research used a qualitative method with a descriptive narrative approach from various sources, articles, websites, and news. The findings from this research through multi-track diplomacy, which focuses on track one (state) and track two (non-state actors), showed that the relevant actors succeeded in turning the Maros Pangkep Geopark into a UGG. The announcement was made at a council meeting in Thailand on September 4, 2022, followed by an official announcement on May 24, 2023, based on decisions taken at the 216th UNESCO Executive Board Session in Paris.